Serie Juglares Pablo Flórez Camargo (2020)
This material consists of four works, arranged for choir, by the Cienagaorense Master Pablo Flórez Camargo. Its main objective is to support the development of techniques specific requirements for singing and choral performance, with musical resourcesof context; also, it is intended to spread the work of the teacher beyond regional borders and insert it in academic settings.